Farm Crisis or Agricultural System Crisis? Defining National Problems in a Global Economy - Glenna, Leland (The International Journal of Sociology of Agriculture and Food, 2003)
The popular press, farm groups, and the Federal Government characterized the 1980s as a period of severe farm crisis. But the decline in farm numbers in the 1980s was not as steep as it had been in the 1950s, 1960s, or even the 1970s. Sociologists recognize that social problems are not the result of the sudden awareness of objective and identifiable conditions, but become defined through a collective process that assigns social significance to a set of conditions. What remains open to examination is how social systems and changes in those systems tend to structure the collective problem-definition process in such a way that one set of actors is able to promote its definitions over others. Using congressional hearings leading up to the passage of the 1985 Food Security Act and United States Department of Agriculture (USDA) data on agricultural conditions in the 1980s, I argue that policy makers defined those conditions as an agricultural system crisis, not as a farm crisis. This choice of definitions reflected the ability of emerging transnational agribusinesses to convince policy makers that the pressures of an international economy required a restructuring of the national farm policies. I will then discuss how these findings improve our understanding of how the state negotiates its national responsibilities in a global economy.